2020
DOI: 10.3390/ijms21155420
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methyltransferase 1 (DNMT1) Acts on Neurodegeneration by Modulating Proteostasis-Relevant Intracellular Processes

Abstract: The limited regenerative capacity of neurons requires a tightly orchestrated cell death and survival regulation in the context of longevity, as well as age-associated and neurodegenerative diseases. Subordinate to genetic networks, epigenetic mechanisms, such as DNA methylation and histone modifications, are involved in the regulation of neuronal functionality and emerge as key contributors to the pathophysiology of neurodegenerative diseases. DNA methylation, a dynamic and reversible process, is executed by D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Compared to cells treated only with control siRNA, the level of DNMT1 transcripts in cells, transfected with DNMT1 siRNA, was significantly reduced, confirming a successful knockdown ( Figure 2 a). We previously showed that such a siRNA-mediated depletion not only results in reduced transcript levels, but similarly diminishes DNMT1 protein levels within 24 h [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared to cells treated only with control siRNA, the level of DNMT1 transcripts in cells, transfected with DNMT1 siRNA, was significantly reduced, confirming a successful knockdown ( Figure 2 a). We previously showed that such a siRNA-mediated depletion not only results in reduced transcript levels, but similarly diminishes DNMT1 protein levels within 24 h [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…It will be important in the future to evaluate the evolution of the disease prospectively, therapeutic influence and vascular (vascular density through OCTA) and neurodegenerative (RNFL) changes. 39 In the future, a longitudinal approach will be important to clarify if the identified expression differences (1) reflect disease evolution, (2) translate the therapeutic impact, (3) or can help to predict the therapeutic resistance profile. In any case, in the perspective of precision medicine, epigenetic characterization and its relation with non-invasive structural biomarkers like SD-OCT could help clarify the best medicine practice in order to personalize the therapeutic response 12 and avoid permanent retinal lesions and irreversible blindness.…”
Section: Discussionmentioning
confidence: 99%
“…In Huntington disease, DNMT1 knockdown strengthens autophagy, and ameliorates Huntington-induced cytotoxicity. 45 Decrease of autophagy activity is occurring upon aging and thought to contribute to aging-related diseases. It uncovers, upon autophagy induction, de novo DNMT3A-mediated DNA methylation on expression of LC3 results in reduced baseline autophagy activity.…”
Section: Epigenetic Modifications and Autophagy-related Diseasesmentioning
confidence: 99%